Potential nanoparticle applications for prevention, diagnosis, and treatment of COVID‐19. Issue 4 (25th September 2020) - Kusumoputro, Sydney; Tseng, Shannon; Tse, Jonathan; Au, Christian; Lau, Candice; Wang, Xiang; Xia, Tian
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) poses an unprecedented challenge to establish effective methods of prevention and treatment. Nanotechnology has shown excellent potential in its ability to fight a variety of healthcare problems due to nanomaterials' unique physicochemical properties and controlled nano‐bio interactions. Expanding their application to a wide‐range of upstream and downstream approaches is necessary to fight COVID‐19. At different stages of this virus‐caused disease, nanotechnology could offer promising solutions, including a way to combat the large number of fatalities caused by a late‐stage cytokine storm. This mini‐review provides an overview of the recent studies regarding nanoparticles' applications in vaccines, personal protective equipment, sterilization of contaminated environments, diagnostic testing, and cytokine reduction treatment in combating COVID‐19. Abstract : Nanotechnology provides a promising approach to combat multiple facets, ranging from prevention to treatment, of the COVID‐19 pandemic. The unique properties of nanoparticles lend their usefulness and versatility in fighting the coronavirus pandemic. This mini‐review specifically outlines pontential applications of nanoparticles in personal protective equipment, vaccines, sterilization solutions, diagnostic tests, and therapeutic treatment for late‐stage coronavirus patients.